Different characterization of ichabod crane in the legend of sleepy hollow short story by Washington irving and sleepy hollow movie by Andrew Kevin Walker - Kholifah Nurmawati (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2014)
ng/rt